2019
DOI: 10.1016/j.jds.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Asthma medication increases dental caries among children in Taiwan: An analysis using the National Health Insurance Research Database

Abstract: Background/purposeAsthma is a common, chronic disease that causes respiratory symptoms in children. Dental caries is also a common chronic disease in the pediatric population. Therefore, the aim of the present study was to investigate the correlation between asthma medications and dental caries among children in Taiwan.Materials and methodsThe Taiwan National Health Insurance Research Database was used in this retrospective cohort study to analyze the correlation between asthma and dental caries in children. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Although these values are lower than those in other studies [ 25 , 26 ], long-term medication is a risk factor for developing early caries. According to a retrospective cohort study conducted in Taiwan, children with asthma and receiving medications had higher dental caries prevalence and higher rate of severe caries than children without asthma [ 27 ]. In our study, having a long-term disease does not seem to increase the caries score in children.…”
Section: Discussionmentioning
confidence: 99%
“…Although these values are lower than those in other studies [ 25 , 26 ], long-term medication is a risk factor for developing early caries. According to a retrospective cohort study conducted in Taiwan, children with asthma and receiving medications had higher dental caries prevalence and higher rate of severe caries than children without asthma [ 27 ]. In our study, having a long-term disease does not seem to increase the caries score in children.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment for asthma is the inhalation of steroids, and this is an important causal factor in the development of dental caries, because of the direct changes in the salivary composition that occur [79][80][81]. Several factors contribute to the increased prevalence of dental caries in asthmatic patients, such as a reduced saliva flow caused especially by beta-2 adrenergic agonists, increased counts of Streptococcus mutans and Lactobacillus spp., and a decreased salivary pH below the critical value 30 min after treatment with beta-2 agonist inhalers [22,36,73,82].…”
Section: Asthma and Dental Cariesmentioning
confidence: 97%
“…Considering the manifestations of this disease, patients with asthma can receive shortterm treatment for constant exacerbations of the pathology, as well as long-term treatment for its maintenance and control, as described in Figure 1 [20,21]. The prescribed anti-asthmatic medication is selected in relation to the severity of the disease and the type of asthma present [22]. There are national and international guidelines, such as those of the Global Initiative for Asthma (GINA), the National Asthma Education and Prevention Program (NAEPP), and the British Thoracic Society (BTS) [23,24], which provide recommendations on the diagnosis and treatment of asthmatic patients on an individualized basis by considering not only the severity of the disease, but also the phenotypic characteristics of the patient [2].…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] It has been reported that inhaler drugs cause periodontal disease, tooth decay and erosion in children with asthma due to their effects on salivary secretion and pH. 53,54 Oral and dental problems are seen as an important cause of comorbidity in patients receiving inhaled corticosteroid therapy. 50,55,56 Possible effects due to the use of inhaled drug groups should be taken into consideration when evaluating oral findings in individuals with chronic respiratory disease.…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%